Prejuicios y homosexualidad, el largo camino hacia la adopción homoparental. Especial atención al caso colombiano (2018)
This article addresses the issue of discrimination, which is generated by prejudices against the people with non-hegemonic sexual orientation or gender identities, who due the social dynamics have had to demand their rights in the courts. It specially focuses on the possibility of the adoption when both parents are of the same-sex (LGBT parenting), considering prima facie the adoption as a right of the children and teenagers, which entails as secondary effect the possibility for men and women, regardless of their sexual orientation or their gender identity, to have a son or a daughter, and so to establish a parent-child relationship protected by law. © 2018, Universidad de Talca. All rights reserved.